IL-8, IL-10, TGF-β, and GCSF Levels Were Increased in Severe Persistent Allergic Asthma Patients with the Anti-IgE Treatment - Arzu D. Yalcin; Atil Bisgin; Reginald M. Gorczynski (Mediators of Inflammation)
Background. Allergic asthma is showed an increase in Th2-cytokine and IgE levels and an accumulation activation of Th2 cells, eosinophils and mast cells. However, recent studies focused on cell-based mechanisms for the pathogenesis of allergic asthma. Objectives. In this study, we compare the anti-IgE treatment modality in the dynamics of immune system cytokine levels in severe persistent asthma (SPA) patients who had no other any allergic disease, newly diagnosed allergic asthma patients and healthy volunteers. Study Design. The study population consisted of 14 SPA patients, 14 newly diagnosed allergic asthma patients and 14 healthy volunteers included as controls. Cytokine levels were measured. Total and specific IgE levels of anti-IgE monoclonal antibody treated patients, serum high-sensitivity C-reactive protein (hsCRP) levels, FEV1/FVC rates and asthma control test (ACT) were measured for the clinical follow-up. Results. We observed that SPA patients presented increasing levels of IL-8, IL-10, TGF-β and GCSF during the anti-IgE treatment in period of sampling times at 4 months and 18 months. However this increase was not correlated neither with serum hsCRP levels nor FEV1/FVC rates. Conclusions. Our study gives a different perspective for the SPA and anti-IgE immunotherapy efficacy at the cell cytokine-linked step.